The Tourist Attractions in Curitiba - PR: An overview by Guia Brazil Quatro Rodas - Franciele Cristina Manosso; Camila Bizinelli; Cinthia Maria de Sena Abrahão; José Manoel Gonçalves Gândara (Revista Brasileira de Pesquisa em Turismo, 2015)
The tour guides books can be worked as relevant instruments for the dissemination of destinations, because encompass information about the destinations' attractions, equipment, infrastructure and tourism services. Then, the tourist can through this, conceiving a destination’s image that will visit, because with the elements worked by the guides, they can get a comprehensive view of what is offered by the destination. Therefore, this article has as objective the analysis of the tourist attractions in Curitiba’s city, according to Guia Brazil Quatro Rodas, presented in the years 1989, 2001, 2013. Thus, the paper aims to also highlight how the document presents the city to its visitors, analyzing the description and the photographs that are showing Curitiba to the tourist. For this, was used as methodology the literature's and documents' research, the latter being applied to observe which attractions, description, and photos were used in the dissemination of Curitiba in the Guia Brazil. As the study results, it can be noted that there was an increase in the number of tourist attractions in Curitiba presented by Guia Brazil Quatro Rodas, and some of these have progressed in the respect of their classification, in the other words, they have improved in quality. Another issue is the publication’s evolution in question the destinations’ presentation to the reader, because more information came to be published, and also began to be used photos to show to the tourist the Curitiba destination.